2022
DOI: 10.3389/fmed.2022.955560
|View full text |Cite
|
Sign up to set email alerts
|

Fluoxetine-induced perinatal morbidity in a sheep model

Abstract: Selective serotonin reuptake inhibitors (SSRI) are the most common antidepressants used by pregnant women. However, adverse pregnancy outcomes have been described in women taking SSRI during pregnancy—placental lesions, premature birth, poor neonatal adaptation. We aimed to investigate the effects of fluoxetine (Prozac® most commonly used SSRI) treatment during the last month of gestation on pregnancy complications, placental and neonatal health in a non-depressed sheep model. On day 119 ± 1 postbreeding (expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…These placental alterations in sheep, and likely in women, appear to be due to fluoxetine inhibition of SERT leading to increased circulating serotonin-producing vasoconstriction of uteroplacental vessels and ultimately restricted blood perfusion to the uterus and placenta (Figure 3). Other authors have also suggested a similar mechanism associating SSRI with increased serotonin altering blood perfusion at the uteroplacental unit affecting placental function and pregnancy outcomes [19,59,[63][64][65][84][85][86].…”
Section: Placental Alterationsmentioning
confidence: 89%
See 4 more Smart Citations
“…These placental alterations in sheep, and likely in women, appear to be due to fluoxetine inhibition of SERT leading to increased circulating serotonin-producing vasoconstriction of uteroplacental vessels and ultimately restricted blood perfusion to the uterus and placenta (Figure 3). Other authors have also suggested a similar mechanism associating SSRI with increased serotonin altering blood perfusion at the uteroplacental unit affecting placental function and pregnancy outcomes [19,59,[63][64][65][84][85][86].…”
Section: Placental Alterationsmentioning
confidence: 89%
“…Although the interpretation of reproductive and neonatal outcomes in animals can be challenging due to differences in the number of offspring per gestation, gestation length, and stage of fetal development at birth, animal models are crucial for understanding the effects of drugs in humans. Multiple animal models have been used to investigate the impact of SSRI on pregnancy outcomes and neonatal health: rodents [52,[59][60][61][62], sheep [63][64][65][66], and fish [67,68]. Additionally, mutant mouse models with altered SERT expression and/or function have been useful to shed light on the role of SERT on pregnancy outcomes and neonatal health [12,31,69,70].…”
Section: General Perspectivesmentioning
confidence: 99%
See 3 more Smart Citations